Strategi Efektif untuk Mengurangi Kesenjangan Pendidikan: Tinjauan Literatur pada Intervensi Global - Muhammad Masykur Abdillah; Miftahul Ulum; Loso Judijanto (Jurnal Ilmiah Edukatif, 2024)
An effective strategy to reduce education disparities is a coordinated effort that combines systemic approaches and direct interventions to ensure equitable access to quality education for all students. Systemic approaches include education policy reform and teacher quality improvement, while direct interventions include financial aid and inclusive education programmes. Collaboration between various stakeholders is also considered important to address the factors that cause education disparities. The results of this study show that a combination of systemic approaches and direct interventions are needed to achieve significant results. Systemic approaches, including education policy reform and teacher quality improvement, are crucial to creating inclusive and sustainable education. Direct interventions, such as the provision of scholarships and financial aid, are important to improve accessibility for disadvantaged students. In addition, partnerships between the government, non-governmental organisations and the private sector are considered vital in addressing the various factors causing disparities. Then, this study emphasises the need for continuous evaluation and adjustment of evidence-based strategies to ensure fair and equitable education for all children.